Visual control training in basketball shooting - Oudejans, R. R. D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
In this presentation I will present our work on visual control training in basketball shooting. In general perceptual training may provide an addition to training that may be used to speed up the acquisition of perceptual-motor expertise in sport settings. In our research on basketball jump shooting we investigated visual control training to improve shooting performance of elite basketball players. In several studies vision of junior male, wheelchair male, and female basketball players was manipulated during shot training in such a way that they were forced to use the information that has been shown to be most relevant for visual control of their basketball shot. Vision was initially manipulated by screens that occluded the vision of the basket during the early parts of the shot, while information became available during the final instances just before ball release (players could look over or from underneath [wheelchair] the screen), providing the shooters with a time window of vision that was necessary and sufficient for accurate shooting. In recent studies vision was manipulated during shot training using Plato liquid-crystal goggles that were wirelessly and manually controlled by the experimenter using a sender/ receiver system. During the training the goggles were only open during the final instances of each shot forcing players to use optimal information. Generally the visual control training led to higher shooting percentages showing that visual control training in which vision is systematically manipulated, either using screens or special occlusion goggles, provides a promising tool to be used in sports practice to improve performance.